THE FINANCIAL MARKET FUNCTIONING PARADIGM IN THE CONDITIONS OF DIGITAL SOCIETY - A. Kravchenko (Наукові горизонти, 2020)
The article provides the substantial analysis of theoretical and methodological paradigm representing the functioning of the financial market in the conditions of digital society. The purpose of the study is to explore the modern paradigm of the financial market functioning in the digital environment. The research framework involves complex, systemic, cybernetic approaches, the methods of modeling, grouping, abstract-logical and synergistic analysis. The article investigates the functioning of financial market in the conditions of digital society, in particular it reveals the essence of the concept "paradigm", "market paradigm" as well as analyses the hypotheses of an effective financial market. The results of the research enable to shape the modern framework of financial market functioning in the digital environment with the conceptual provisions consisting in the legal framework improvement; institutional optimization of the financial market through unification, consolidation, changes in organizational and legal forms; optimization of the financial transactions structure, promotion of business activity, improvement of financial risk management methods; ensuring integrity, transparency, effective regulation and the like. The principles of the financial market functioning in digital conditions are distinguished including transparency of financial processes; financial and legal freedom of the subjects; effective functioning; stability; dynamic development; effective regulation; digitization of financial transactions and digitization of property rights. A promising area of further research is to study the issues of functional features of the financial market in the conditions of digital transformation of the society.